Hoax Dalam Perspektif Islam - Abd Wahid (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2017)
The flow of information that flows so swiftly in social media makes some people can not sort out which news is right and wrong or hoax. Broadcast feature in the chat and share applications on social networking into a means that makes false news spread faster to viral. Hoax is the same as lying. Spreading the word hoax means spreading false news. Of course, Islam does not justify its people to do this. Islam strongly condemns the actions that lead to lies. Especially to spread the false news. Islam is deeply condemned and a grave sin for the perpetrators. Because, spreading false news can upset the community and ravage unity. Therefore, Islam teaches to inspect the truth of the news. Clarify all the information obtained, so as not to fall into slander.